Türkiye-Azerbaycan ilişkilerinin siyasi ve ekonomik boyutları ve kamu diplomasisi - DERMAN, GİRAY SAYNUR (My University, 2022)
Azerbaycan’ın 9 Kasım 1991’de bağımsızlığını ilan etmesinden sonra Türkiye en önemli ve kültürel olarak en yakın ülke oldu. Türkiye genç cumhuriyeti tanıyan ilk devletti. Ankara’da o dönem Adriyatik Denizi’nden Çin Seddi’ne uzanan bir Türk dünyasından söz ediliyordu. Azerbaycan’ın ilk cumhurbaşkanı Ayaz Mutəllibov’un temkinli hareket etmesi nedeniyle 1992 yılına kadar karşılıklı ilişkiler yavaş gelişti. Türkiye’nin bu aşamadaki öncelikleri, Azerbaycan’ın bağımsızlığını tanımak, Bakü’de Türkiye ile işbirliğine dayalı bir hükümetin tesis edilmesi, Güney Kafkasya’da Rus hâkimiyetini engellemek, Dağlık Karabağ’da Azerbaycan egemenliğini sürdürmek ve Azerbaycan petrol anlaşmasında pay sahibi olmaktı. Elçibey dönemi ve sonrasında gelişen bir millet iki devlet anlayışı çerçevesinde günümüzde dostluk, kardeşlik çerçevesinde iki ülke ilişkileri günden güne gelişmektedir. Bu çalışmada Türkiye-Azerbaycan ilişkilerinin kamu diplomasisi çerçevesinde siyasi ve ekonomik boyutları incelenmiştir. Öncelikle Azerbaycan’ın bağımsızlığından sonra Türkiye ile Azerbaycan arasındaki siyasi ilişkilerin gelişimi ele alınmıştır. Makale kapsamında Türkiye ve Azerbaycan ekonomileri ve enerji sektörleri Dağlık Karabağ sorunu ve Türkiye’nin Ermenistan ile ilişkilerindeki normalleşme sürecinin Türkiye-Azerbaycan ilişkilerine etkileri incelenmiştir. Türkiye ile Azerbaycan arasındaki ekonomik ilişkiler karşılaştırmalı olarak analiz edilmiştir.

After Azerbaijan declared its independence on November 9, 1991, Turkey became the most important and culturally closest country. Turkey was the first state to recognize the young republic. In Ankara at that time, there was talk of a Turkish world stretching from the Adriatic Sea to the Great Wall of China. Mutual relations developed slowly until 1992, due to the cautious action of Azerbaijan’s first President Ayaz Mutəllibov. Turkey’s priorities at this stage were to recognize the independence of Azerbaijan, to establish a government based on cooperation with Turkey in Baku, to prevent Russian domination in the South Caucasus, to maintain Azerbaijani sovereignty in Nagorno-Karabakh and to have a stake in the Azerbaijan oil agreement. The relations between the two countries are developing day by day within the framework of friendship and brotherhood, within the framework of the understanding of one nation, two states that developed during and after the Elçibey period. In this study, political and economic dimensions of TurkeyAzerbaijan relations within the framework of public diplomacy have been examined. First of all, the development of political relations between Turkey and Azerbaijan after the independence of Azerbaijan was discussed. Within the scope of the article, the Turkish and Azerbaijani economies and energy sectors, the Nagorno-Karabakh conflict and the effects of the normalization process in Turkey’s relations with Armenia on Turkey-Azerbaijan relations were examined. The economic relations between Turkey and Azerbaijan were analyzed comparatively.
Political and economic dimensions of Turkey-Azerbaijan relations and public diplomacy
Keywords: government based on cooperation with Turkey in Baku; to prevent Russian domination in the South Caucasus; to maintain Azerbaijani sovereignty in Nagorno-Karabakh and to have a stake in the Azerbaijan oil agreement. The relations between the two countries are developing day by day within the framework of friendship and brotherhood; within the framework of the understanding of one nation; two states that developed during and after the Elçibey period. In this study; political and economic dimensions of TurkeyAzerbaijan relations within the framework of public diplomacy have been examined. First of all; the development of political relations between Turkey and Azerbaijan after the independence of Azerbaijan was discussed. Within the scope of the article; the Turkish and Azerbaijani economies and energy sectors; the Nagorno-Karabakh conflict and the effects of the normalization process in Turkey’s relations with Armenia on Turkey-Azerbaijan relations were examined. The economic relations between Turkey and Azerbaijan were analyzed comparatively; Türkiye; Azerbaycan; Dağlık Karabağ; Enerji; Ekonomi; Kamu Diplomasisi